Mengoptimalkan Digitalisasi UMKM: Peran Kompetensi SDM, Skala Usaha dan Fasilitas Infrastruktur - Ladewi, Yuhanis; Sabrina, Nina; Ayati, Summi (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
This study aims to determine and partially analyze the effect of human resource competency, size of MSMEs, and availability of infrastructure on the implementation of digitalization in MSMEs. The type of research used in this research is associative research. The population in this study was 54 MSMEs with 108 respondents. Data collection using questionnaires. Data testing using validity and reliability tests. The data analysis technique used is multiple linear regression analysis. The analysis technique in this study used the statistical computer program SPSS. The results of this study can be concluded partially indicating that the the human resource competency, size of MSMEs and availability of infrastructure have effect on the implementation of digitalization in MSMEs.